Trends of Healthy Lifestyles Among Adolescents: An Analysis of More Than Half a Million Participants From 32 Countries Between 2006 and 2014 - Priscila Marconcin; Margarida G. Matos; Margarida G. Matos; Andreas Ihle; Andreas Ihle; Andreas Ihle; Gerson Ferrari; Élvio R. Gouveia; Élvio R. Gouveia; Marcos López-Flores; Miguel Peralta; Miguel Peralta; et al. (Frontiers Media S.A., 2021)
The purpose of this study was to provide data regarding the prevalence and trends of adolescents' healthy lifestyles from 32 countries between 2006 and 2014 by sex and age interval. The data used in the present study were derived from the Health Behavior in School-aged Children (HBSC) 2006, 2010, and 2014 international database. Healthy lifestyle was assessed using the combination of daily physical activity, daily fruit and vegetable consumption, <2 h daily on screen-based behaviors, abstinence from alcohol, and abstinence from tobacco products. Healthy lifestyle measures were based on self-report. The final sample comprised 519,371 adolescents (aged between 10 and 16 years old). The prevalence of healthy lifestyle behaviors increased between 2006 and 2014. The healthy lifestyle score worsened with advancing age for boys and girls. Comparing countries, for boys, the highest values were observed in adolescents from Ireland (5.2%, 95% CI: 3.9, 6.4), and for girls, the highest values were observed in adolescents from Iceland (4.2%, 95% CI: 3.6, 4.7). The present study showed a slight trend to an improved healthy lifestyle among adolescents, although much more has to be done. A joint effort from multiple areas of knowledge must be made to improve adolescent health policies, since lifestyles in adolescence play an important role for the development of vulnerability and health in later life.